Nasab Anak Luar Kawin Pasca Putusan Mahkamah Konstitusi Nomor 46/PUU-VIII/2010 - Hamzani, Achmad Irwan (Mahkamah Konstitusi Republik Indonesia, 2015)
Constitutional Court Decision No. 46/PUU-VIII/2010 granted the petition Machica Mochtar, who is married with Moerdiono the Islamic religion in accordance, but not recorded. If the marriage was born a boy named Mohammed Iqbal Ramadan. After the decision of the Court, the status of illegitimate children has a civil relationship with his father and his father’s family. Child outside marriage include children born of the marriage legitimate religion, but not recorded, and the children born from adultery. According to Islamic law, the Constitutional Court’s decision is appropriate when applied to the child of a valid marriage according to religious but not registered. Meanwhile, when applied to children outside marriage, adultery result, the Court’s decision is contrary to Islamic law.